1993
DOI: 10.3928/0191-3913-19930901-08
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of Medial Rectus Muscle to the Original Insertion for Consecutive Exotropia

Abstract: Twenty-four patients who underwent surgery to correct consecutive exotropia that developed iatrogenically after surgical overcorrection were studied retrospectively. All patients underwent single or bilateral advancement of the medial rectus muscle to the original muscle insertion. The mean preoperative exodeviation was 26.7 prism diopters at distance and 3S.2 Δ at near. Postoperatively, in cases receiving advancement of a single medial rectus, the mean amount of correction was 23.2 Δ at distance and 29.6 Δ at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Our success rate is compatible with numerous studies. 13,25,26,28 But, the improvement amounts of deviation is slightly <23 PD obtained by Marcon and Pittino. 15 We can explain this result by the studies of Kim et al, 13 Cho and Ryu, 14 who reported the positive relationship between the preoperative deviation and the effect of the advanced muscle.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our success rate is compatible with numerous studies. 13,25,26,28 But, the improvement amounts of deviation is slightly <23 PD obtained by Marcon and Pittino. 15 We can explain this result by the studies of Kim et al, 13 Cho and Ryu, 14 who reported the positive relationship between the preoperative deviation and the effect of the advanced muscle.…”
Section: Discussionmentioning
confidence: 80%
“…Medial rectus advancement alone may be adequate and efficient for correcting small angle consecutive XT, after recession of MR for ET. [13][14][15][25][26][27] Biedner et al 27 has suggested MR advancement alone up to the primary location for 25 PD and smaller deviations. However, in some studies 25,28 after MR advancement, it has been reported that the success rates have decreased over time and the exodeviation recurs.…”
Section: Discussionmentioning
confidence: 99%
“…While Ohtsuki et al preferred the standard reversal of the primary operation for esotropia, 20 Patel et al recommended recession of the unoperated lateral rectus muscle as it provided successful results with fewer complications, particularly in patients who did not have an adduction deficit. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Cooper had the principle that consecutive exotropia cases should be managed as a new case with anatomical alterations regardless of the previous esotropia surgery that had taken place. 1 While Ohtsuki et al preferred the standard reversal of the primary operation for esotropia, 20 Patel et al recommended recession of the unoperated lateral rectus muscle as it provided successful results with fewer complications, particularly in patients who did not have an adduction deficit. 21 Proper surgical management should be performed after meticulous examination, careful assessment of the type and extent of previous surgical procedures, and the presence or absence of limited adduction.…”
Section: Discussionmentioning
confidence: 99%